Manuka Honey Reduces the Virulence of Pectobacterium brasiliense by Suppressing Genes That Encode Plant Cell Wall-Degrading Enzymes - Sheila Ava; Siti Subandiyah; Muhammad Saifur Rohman; Naoto Ogawa; Tri Joko (ASEAN Journal on Science and Technology for Development, 2022)
The primary virulence of soft rot pectobacteria, including Pectobacterium brasiliense, is mainly determined by the massive production of plant cell wall-degrading enzymes (PCWDEs), which promote plant tissue maceration in many crops. The antibiotic treatment to treat bacterial soft rot causes environmental problems and potentially affects resistance. Antibiotic resistance is driving interest in antimicrobial treatments, and no organism has been reported to have acquired resistance to honey. However, the use of honey as a therapeutic agent for plant bacterial pathogens has rarely been studied. Therefore, this study was undertaken to determine the in vitro effect of Manuka honey against P. brasiliense at the phenotypic and genotypic levels. A sublethal concentration of honey was determined by a growth inhibition assay in broth medium containing different concentrations of Manuka honey. A macerating assay was performed on orchid leaves, and the activities of the PCWDEs were examined in plate assays. The expression of PCWDE-associated genes was investigated using semi-quantitative reverse transcription-polymerase chain reaction analysis. The exposure of P. brasiliense to a sublethal concentration of Manuka honey significantly decreased the maceration ability of the orchid and the synthesis of PCWDEs, i.e., pectate lyase, polygalacturonase, and protease. Moreover, five PCWDEs-encoding genes, such as pelA, pelB, pelC, pehA, and prtW, had lower expression levels after the honey treatment compared with recA as the internal standard. The honey treatment decreased the virulence of P. brasiliense associated with the synthesis of PCWDEs. Therefore, Manuka honey reduced virulence by suppressing the expression of the PCWDE genes.